INDO BLACK MAGIC: DAYA PIKAT PEREMPUAN INDONESIA DALAM LAGU JEBUNG & BASBOI - Saragupita, Angela Tanjung (Universitas Lancang Kuning, 2024)
Jebung or Jessice Bunga is a newcomer singer whose songs are always unique. One of the songs entitled 'Indo Black Magic' has a theme related to pellets/witchcraft which is still believed by some Indonesian people. This research aims to find out how the image of Indonesian women is depicted in the Jebung song which is related to local myths in Indonesian society. This type of research is qualitative research where this research uses the concept of descriptive content analysis. The research data is in the form of lyrics to the song 'Indo Black Magic' sung by Jebung and Basboi, lyrics transmitted directly from ACUAN Entertainment's YouTube channel without changing the vocabulary and spelling. The data collection technique uses listening and note-taking techniques, then the data is analyzed based on Sara Mills' feminist studies and Roland Barthes' semiotic studies. The results of the research show that there are depictions of Indonesian women who are described based on their ethnicity, including Minang, Batak, Balinese, Dayak and Sundanese. In each lyric, Jebung also inserts a message for women to be confident and proud of the natural beauty they have. Indonesian women don't need to use pellets/witchcraft to attract men, because their charm already radiates and is able to hypnotize anyone who looks at them. Basboi as a rapper also shows his appreciation for Indonesian women who he likens to the natural beauty of Sumba. He values ​​Indonesian women like treasures that must be protected.